The role of ncRNAs in neuroblastoma: mechanisms, biomarkers and therapeutic targets - Shaohui Huang; Naying Gong; Jiangbin Li; Mingye Hong; Li Li; Ling Zhang; Hua Zhang (BMC, 2022)
Abstract Neuroblastoma (NB) is a malignant tumor in young children that originates from the neural crest of the sympathetic nervous system. Generally, NB occurs in the adrenal glands, but it can also affect the nerve tissues of the neck, chest, abdomen, and pelvis. Understanding the pathophysiology of NB and developing novel therapeutic approaches are critical. Noncoding RNAs (ncRNAs) are associated with crucial aspects of pathology, metastasis and drug resistance in NB. Here, we summarized the pretranscriptional, transcriptional and posttranscriptional regulatory mechanisms of ncRNAs involved in NB, especially focusing on regulatory pathways. Furthermore, ncRNAs with the potential to serve as biomarkers for risk stratification, drug resistance and therapeutic targets are also discussed, highlighting the clinical application of ncRNAs in NB.